THE METHOD OF USING MS EXCEL TO CALCULATE THE REGRESSION EQUATIONS OF FULL FACTORIAL EXPERIMENT WHILE INVESTIGATING PROPERTIES OF WATER-GLASS MIXTURESI - S. D. Dingilevsky (Литьë и металлургия)
It is shown that the use of MS excel enables reduce time to find the regression coefficients in the calculations of similar matrices, and also simplifies the process of charting the influence of factors on the studied properties of the experiments.